The Promising IgSF11 Immune Checkpoint Is Highly Expressed in Advanced Human Gliomas and Associates to Poor Prognosis - Ghouzlani, Amina; Rafii, Soumaya; Karkouri, Mehdi; Lakhdar, Abdelhakim; Badou, Abdallah (Frontiers in Oncology, 2021)
Glioma is the most prevalent primary brain tumor. Immune checkpoint blockade has made a great stride in mending patient’s clinical outcome for multiple types of cancers. However, PD-1, CTLA-4, or VEGF blockade exhibited only poor outcome in glioma patients. This study aimed to explore the expression and role of IgSF11, an emerging immune checkpoint and a ligand of VISTA, in human gliomas. IgSF11 mRNA expression was assessed in human glioma patients at different grades using 2 independent cohorts, a set of 52 Moroccan samples, including 20 glioma tissues, 22 PBMC samples taken before and 10 PBMC samples taken after surgery; and a series of 667 patients from TCGA. In parallel, immunohistochemistry was performed to evaluate IgSF11 protein staining. IgSF11 gene expression was significantly upregulated in high grade glioma tissues, compared to low grade. IgSF11 protein also showed a significant expression in low and high-grade gliomas. Interestingly, IgSF11 expression seemed to correlate positively with other critical immune checkpoints such as PD1, PDL-1, VISTA, and surprisingly negatively with CTLA-4. Although, T cell markers appeared higher in advanced gliomas, T cell-produced pro-inflammatory genes showed similar expression levels, highly likely because of the potent immunosuppressive microenvironment. Indeed, increased expression of IgSF11 in advanced human gliomas associated with a poor overall survival. Our data strongly suggest that IgSF11 is an immune checkpoint, which is upregulated in advanced human gliomas and contributes to the immunosuppressive state resulting in a poor clinical outcome in glioma patients. IgSF11 could be considered as a possible promising therapeutic target in advanced human gliomas.